Predictors of Brand Equity in the Contemporary Markets - Khan, Ali Junaid; Farooq, Fatima; Bakar, Abou; Murad, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2022)
Brand equity development has become a challenge for modern brands. Marketing innovation and changing consumer value perceptions are causing consumers to leapfrog, posing a challenge for brand equity development. The data for this study was collected with random sampling techniques. 450 respondents were considered to collect data on the Likert scale questionnaire. The Partial Least Square (PLS) method of data analysis was used in this study for data analysis. According to the findings of the study, brand personality, customer satisfaction, consumer lifestyle, marketing innovation, and consumer changing value perception all have a significant impact on brand equity. The significant framework of this study is a contribution to the body of knowledge as it describes the significant relationship between different variables critical for brand equity development. Furthermore, this study provides business implications for brands working in Pakistan to improve brand equity with realistic results to influence the consumers for brand equity.